Combining ability and heterosis for fibre yield traits in Nigeria kenaf (Hibiscus cannabinus L.) Collections (2014)
Kenafas a renewable fibre crop is known to yield lower in Nigeria than in other countries of the world. An experiment was conducted at the University of Ibadan, Oyo State, Nigeria, where sixteen (16) crosses were made among four (4) Nigeria kenaf (Hibicuscannabinus) accessions to investigate the combining ability and heterosis for fibre yield traits in the hybrids. The parents and progenies were planted in three replicates in a randomized complete block design. Data were collected on plant height, stem diameter and girth at flowering and at harvest, as well as stalk weight at harvest and means separated at P=0.05. Results showed no significant differences among genotypes at flowering and for stalk weight at harvest. Higher general combining ability (GCA) over specific combining ability (SCA) was recorded for all characters at harvest. Only accession NHC 10(1) had a positive GCA for height at harvest (21.84) and girth at harvest (1.09). The highest SCA effects were recorded in cross NHC 10(1) X NHC 2(2) for all measured traits. In contrast, the highest positive mid-parentheterosis (28.02%) was obtained in the reciprocal cross NHC 15 X NHC 10(1)followed by NHC 2(2) X NHC 10(1) (25.76%) for HAH. Both crosses had parent NHC 10(1) to be one of their respective parents. Thus, this study identified hybrids NHC 15 X NHC 10(1) and NHC 2(2) XNHC 10(1) as promising for improvement of fibre yield traits. However, performances of these hybrids need to be evaluated in multi-locational and on-farm trials prior to commercial use.